Approaches to solving problems encountered by teachers and students in secondary school biology practical class in Nigeria (2014)
Science is valuable both in acquisition of knowledge and in vocational training. The role played' by science cannot be overemphasized as the bedrock on which the bulk of present technological innovations are built. Biology is a science subject that deals with all living things and their existence as well as relationship with non-living things. In spite of the importance of the subject, students had shown continuous under achievement in the subject in secondary school level over the years which can be attributed to poor performance in practical examination. This study, investigated problems encountered by teachers and students in practical biology among secondary school students in Nigeria. Four research hypotheses were tested at 0.05 significance of difference. The study adopts an ex-post facto research design. Sample consisted of One thousand and three hundred (1,300) students and One hundred and thirty (130) Biology teachers from the selected schools. Two validated instruments: Biology Teachers Questionnaire on Practical Work (0.78) and Students Questionnaire on Practical Work in Biology (0.82) were used. Data collected were analysed using descriptive and inferential statistics. There is a significant difference in the perception of problems encountered in practical work in Biology by both teachers and students (t= 9.052, degree of freedom, df = 211; p< 0.05). Moreover, there is no significant relationships between teachers’ and students’ perception of problems encountered in practical work in Biology (r=-0.031, p>.05). Findings from the study are an eye opener to the problems encountered by teachers and students in practical biology. Regular seminar and workshops should be organized for teachers so as to incorporate into them new ideas and innovation for effective practical teaching.